Efektifitas Learning Management System di Beberapa Universitas Indonesia Pada Masa Pandemi - Sugiyanti Sugiyanti; Yutri Amelia; Dwiza Riana; Sri Hadianti (Program Studi Teknik Informatika Universitas Nusa Putra, 2023)
The pandemic that has hit almost all countries has limited human movement, and so has Indonesia. The pandemic has affected many sectors, especially the economy, and business, and one of them is education. At the beginning of the pandemic era, the education system in Indonesia implemented the distance learning method, and now, some universities are still implementing it. Several campuses in Indonesia utilize the Learning Management System (LMS) to support distance learning, in which the learning process can take place and be as effective as face-to-face learning. This research uses quantitative methods to focus on the effectiveness of LMS at several Indonesian universities during the pandemic. One hundred thirty-four students from 41 universities in Indonesia participated in this study. The results of this study are that online assessment, online teaching effectiveness, and online support do not significantly affect student online learning satisfaction. In contrast, gender does not significantly affect learning satisfaction and intention to use online learning with LMS.